Impact of Humanitarian Law Violations in The World War Against The Establishment of International Legal Instruments - Efendi, Didik; Purnawan, Aris; Susilo, Tarsisius; Sirait, Dinand Tumpak; RS , Wahyu (Jurnal Indonesia Sosial Sains, 2025)
World War I (1914–1918) and World War II (1939–1945) marked pivotal moments in the development of International Humanitarian Law (IHL), as they vividly demonstrated the destructive impact of armed conflict on humanitarian values. Serious violations of IHL, such as the use of chemical weapons, mass killings, inhumane treatment of prisoners of war, and acts of genocide, revealed the limitations of existing international legal instruments and prompted the establishment of a stronger legal framework. This study aims to analyze the forms of IHL violations during the world wars, examine the international community's responses to those violations, and evaluate their influence on the formation of modern international legal instruments, such as the 1949 Geneva Conventions, the 1977 Additional Protocols, and the establishment of the International Criminal Court (ICC). Utilizing a normative juridical and historical approach, this research demonstrates that the humanitarian tragedies of the world wars served as critical catalysts for strengthening international legal standards to ensure the protection of conflict victims and uphold accountability for war crimes.